Biohydrogen production for sustainable energy transition: A bibliometric and systematic review of the reaction mechanisms, challenges, knowledge gaps and emerging trends - Umunnawuike, Chika; Siti Qurratu’ Aini, Mahat; Nwaichi, Peter Ikechukwu; Money, Barima; Agi, Augustine Aja (Elsevier Ltd., 2024)
Biological hydrogen production is seen as one of the solutions to achieve a sustainable energy transition and net-zero emission by 2050. The underlying mechanisms of biological hydrogen production methods are still tenuous in literature. This study uses bibliometric and systematic literature review methodologies to examine the recent and emerging techniques on biological hydrogen production methods and their reaction mechanisms by evaluating 705 articles in Scopus® database from 2000 to May 2024. Scientific visuals were developed for subject areas, top journals, productive nations, top institutions, leading authors, most cited articles, emerging themes, research areas, and reaction mechanisms. The analysis revealed substantial growth in this research area over the past two decades, with notable shifts observed between 2016 and 2019, indicating strong interest from the scientific community. Exploration of the author's keywords reveals that hydrolysis, acidogenesis, carbon fixation, absorption, and nitrogen fixation are the dominant reaction mechanisms of biohydrogen (bio-H2) production methods. Emerging themes in Bio-H2 production research from Scopus® database query shows four clusters with dark fermentation as the most published bio-H2 production method. Keywords co-occurrence analysis identified hydrogen production, hydrogen, biohydrogen, and fermentation, as the most prevalent. Bioenergy, biofuels, biohydrogen production, fermentation process, wastewater treatment technologies, microbial and biochemical aspects of anaerobic fermentation are the emerging trends for the future. This review acts as a useful resource for researchers, scholars, and practitioners interested in advancing their knowledge of biological hydrogen production. Results obtained from this study can provide valuable information for researchers to identify future hotspots in biological hydrogen production.